Análise de áreas de risco a inundações em ambiente urbano: cidade de Santo Antônio do Tauá (PA) - LEAL, Eloilson Bezerra (2019)
This study identified and analyzed the areas subject to floods in the urban area of the Municipality of Santo Antônio do Tauá, State of Pará, using Geoprocessing techniques. The methodology applied to the study was given through a bibliographical review on the problematic presented and survey of cartographic bases; geomorphological analysis and the river dynamics of the area in question; survey and analysis of laws regulating environmental and urban policy; fieldwork for systematic observations, photographic records and data collection with GPS; and mapping of the mesh and streets and risk areas using the QGIS 3.4 software. In the context of the urban area of Santo Antônio do Tauá (municipal headquarter), the potential risk areas are distributed along the floodplain of the Santo Antônio stream and its tributaries, which correspond to geomorphologically inserted lands in "lowland" environments, where the consolidated and unconsolidated urban area, presenting low topographic gradient, with vulnerability to environmental impact arising from urbanization itself and river dynamics. In this sense, urban planning assumes significant importance due to the presence of occupations that characterize the urban landscape of many Amazonian cities, where its role is to establish the rules of land occupation and, therefore, subsidize actions that can contribute to environmental management in risk areas.